Holoprosencephaly and Pure Red Cell Aplasia in a Feline Leukaemia Virus-Positive Kitten. Issue 2 (February 2016) - Southard, T.L.; Rodriguez-Ramos Fernandez, J.; Priest, H.; Stokol, T.
Summary: A 9-month-old, female, domestic longhair cat with severe anaemia tested positive for feline leukaemia virus (FeLV) and was humanely destroyed and submitted for necropsy examination. Gross findings included a non-divided rostral telencephalon, consistent with semilobar holoprosencephaly. Histological examination of the bone marrow revealed an almost complete absence of erythroid precursor cells, consistent with pure red cell aplasia, and mild to moderate myelofibrosis. This case demonstrates a very unusual central nervous system defect, as well as an atypical presentation of pure red cell aplasia, in a FeLV-positive kitten.